The Influence of Future Cash Flow Predictions on Profits in Companies Listed on the Indonesia Stock Exchange - Titik Purwanti (International Journal of Seocology, 2020)
This research was conducted to determine the effect of future cash flow predictions on profits (gross profit, operating profit, and net income) in food and beverage companies listed on the Indonesia Stock Exchange. The method used in this research used purposive sampling with a population of food and beverage companies listed on the Indonesia Stock Exchange for the period 2016-2018. The samples in this research were 19 companies. The results obtained indicate that the operating profit variable has a partial effect on future cash flows, while the net income variable and the gross profit variable do not partially affect future cash flows. Simultaneously, gross profit, operating profit and net income have an effect on future cash flows.